Scope of e-Business & e-Commerce to Business and Modern Life - Rosita; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
E-commerce & e-business refers to the use of the Internet and the Web to transact business. More formally, e-commerce & e-business is a digital commercial transaction between organizations and individuals. Digital is meant here mostly through the internet and the web. This thing is unique in that it is available anywhere, anytime. Allows you to shop from the desk, home, and workplace. Using the E-commerce market from the market goes beyond traditional boundaries and removes temporal and geographic location. And for customers, it will save costs and time from not having to go to the real market (Ubiquity). E-commerce & e-business enables transactions across cultures and national boundaries more conveniently and effectively (global reach). The technical standards of E-commerce & e-business are universal and this makes consumers reduce their efforts to find which goods are suitable because the product standards are universal.